Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Kemampuan Pemecahan Masalah Matematis dan Motivasi Belajar Siswa pada Materi SPLTV di Kelas X - Tambunan, Lisna; Simanjuntak, Ruth Mayasari; Suarman, Adi (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to analyze the effect of the Problem Based Learning (PBL) learning model on mathematical problem-solving ability and student learning motivation on the Three Variable Linear Equation System (SPLTV) material in class X of SMK Swasta Budi Setia Sunggal Academic Year 2025/2026. This study uses a quantitative approach with a quasi-experimental study design in the form of a posttest-only control group design. The population of this study was all students of class X of SMK Swasta Budi Setia Sunggal consisting of 5 classes. The sample was determined using a purposive sampling technique. The research instruments used were tests, questionnaires, and observation sheets which were tested for validity, reliability, difficulty level, and discriminating power first. Post-test data were analyzed using normality tests, homogeneity tests, t-tests, and effect size. The results showed that the average post-test problem-solving ability in the experimental class reached 51.53 higher than the control class which reached 44.07. Meanwhile, the average post-test results of learning motivation in the experimental class reached 56.53, higher than the control class which reached 50.37. The results of the study showed that there was a significant influence between students' mathematical problem-solving abilities between the experimental class and the control class with a significant value of 0.001 0.05. In addition, there was no significant influence on students' learning motivation between the experimental class and the control class with a significant value of 0.191 0.05. Thus, it can be concluded that the use of the problem-based learning model has a significant effect on problem-solving abilities, while there is no significant influence on learning motivation.